(untitled) - Kranz, Maciej (Hoboken, New Jersey, 2017)
Summary: For business managers, the biggest question surrounding the Internet of Things is what to do with it. This book examines the way IoT is being used today -- and will be used in the future -- to help you craft a robust plan for your organization. Focusing on the business implications of Internet of Things, Kranz describes the sheer impact, spread, and opportunities arising every day, and how business leaders can implement Internet of Things today to realize tangible business advantages.
Keywords: Công nghiệp Internet,Internet industry; Quản lý,Management